Back Cover: Direct Evidence of Subsurface Oxygen Formation in Oxide‐Derived Cu by X‐ray Photoelectron Spectroscopy (Angew. Chem. Int. Ed. 3/2022). Issue 3 (6th December 2021) - Wang, Hsin‐Yi; Soldemo, Markus; Degerman, David; Lömker, Patrick; Schlueter, Christoph; Nilsson, Anders; Amann, Peter
Abstract : Subsurface oxygen in oxide‐derived Cu is evidenced by X‐ray photoelectron spectroscopy, as reported by Hsin‐Yi Wang et al. in their Research Article (e202111021) . The results point out that after reduction of the Cu oxide precursor, two types of oxygen species, (i) oxygen staying at lattice defects and/or vacancies in the surface‐most region and (ii) interstitial oxygen intercalated in the metal structure, are embedded between the fully reduced metallic surface and the Cu2 O buried beneath. This study adds convincing support for subsurface oxygen formation.